miR-126 contributes to Parkinson disease by dysregulating IGF-1/PI3K signaling: miRNAs and IGF-1 signaling in Parkinson disease - Kim, Woori; Lee, Yenarae; McKenna, Noah D.; Yi, Ming; Simunovic, Filip; Wang, Yulei; Kong, Benjamin; Rooney, Robert J.; Seo, Hyemyung; Stephens, Robert; Sonntag, Kai C. (2014)
Dopamine (DA) neurons in sporadic Parkinson disease (PD) display dysregulated gene expression networks and signaling pathways that are implicated in PD pathogenesis. Micro (mi)RNAs are regulators of gene expression, which could be involved in neurodegenerative diseases. We determined the miRNA profiles in laser microdissected DA neurons from postmortem sporadic PD patients’ brains and age-matched controls. DA neurons had a distinctive miRNA signature and a set of miRNAs was dysregulated in PD. Bioinformatics analysis provided evidence for correlations of miRNAs with signaling pathways relevant to PD, including an association of miR-126 with insulin/IGF-1/PI3K signaling. In DA neuronal cell systems, enhanced expression of miR-126 impaired IGF-1 signaling and increased vulnerability to the neurotoxin 6-OHDA by downregulating factors in IGF-1/PI3K signaling, including its targets p85β, IRS-1, and SPRED1. Blocking of miR-126 function increased IGF-1 trophism and neuroprotection to 6-OHDA. Our data imply that elevated levels of miR-126 may play a functional role in DA neurons and in PD pathogenesis by downregulating IGF-1/PI3K/AKT signaling and that its inhibition could be a mechanism of neuroprotection.